A comprehensive study on mechanical properties of Bi1.8Pb0.4Sr2MnxCa2.2Cu3.0Oy superconductors - Doğruer, Musa; Karaboğa, Fırat; Yıldırım, Gürcan; Terzioğlu, Cabir; Öztürk, Özgür (Springer Science and Business Media LLC, 2013)
This study manifests the crucial change in the mechanical performances of Bi1.8Pb0.4Sr2MnxCa2.2Cu3.0Oy superconductor samples (x = 0, 0.03, 0.06, 0.15, 0.3 and 0.6) prepared by conventional solid-state reaction method by use of Vickers microhardness (Hv) measurements carried out at different applied loads, (0.245 N ≤ F ≤ 2.940 N). Load dependent microhardness, load independent microhardness, Young’s (elastic) modulus and yield strength values being account for the potential technological and industrial applications are evaluated from the hardness curves and compared with each other. It is found that the Hv, elastic modulus and yield strength obtained decrease (increase) with the enhancement of the applied load for the undoped (doped) samples. Surprisingly, the results of the Hv values illustrate that the samples doped with x = 0.03, 0.06, 0.15, 0.3 and 0.6 exhibit reverse indentation size effect (RISE) feature whereas the pure sample obeys indentation size effect (ISE) behavior. Furthermore, the experimental results are examined with the aid of the available methods such as Meyer’s law, proportional sample resistance model (PSR), elastic/plastic deformation (EPD), Hays–Kendall (HK) approach and indentation-induced cracking (IIC) model. The results inferred show that the hardness values calculated by PSR and EPD models are far from the values of the plateau region, meaning that these models are not adequate approaches to determine the real microhardness value of the Mn doped Bi-2223 materials. On the other hand, the HK approach is completely successful for the explanation of the ISE nature for the pure sample while the IIC model is obtained to be the best model to describe the hardness values of the doped materials exhibiting the RISE behavior. Additionally, the bulk porosity analysis for the samples reveals that the porosity increases monotonously with the increment in the Mn inclusions inserted in the Bi-2223 system, presenting the degradation of the grain connectivity.